2018
DOI: 10.3389/fpsyg.2018.02171
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis, Parasitism and Bilingual Cognitive Control: A Neuroemergentist Perspective

Abstract: Interest in the intersection between bilingualism and cognitive control and accessibility to neuroimaging methods has resulted in numerous studies with a variety of interpretations of the bilingual cognitive advantage. Neurocomputational Emergentism (or Neuroemergentism for short) is a new framework for understanding this relationship between bilingualism and cognitive control. This framework considers Emergence, in which two small elements are recombined in an interactive manner, yielding a non-linear effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 58 publications
3
20
0
Order By: Relevance
“…This is in line with Klein et al (), who also found that later AoA relates to thicker left SPL, although in their study this was a continuous (not categorical) relationship. The findings of the left SPL, IPL, and STG fit with the argument that late bilinguals in particular may achieve L2 resonance via metacognitive processes that rely on nonlanguage areas (e.g., recoding, rehearsal, and imagery) in order to defend against L1 entrenchment (Berken et al, ; Hernandez, Claussenius‐Kalman, Ronderos, & Vaughn, ; Hernandez, Li, & MacWhinney, ).…”
Section: Discussionsupporting
confidence: 72%
“…This is in line with Klein et al (), who also found that later AoA relates to thicker left SPL, although in their study this was a continuous (not categorical) relationship. The findings of the left SPL, IPL, and STG fit with the argument that late bilinguals in particular may achieve L2 resonance via metacognitive processes that rely on nonlanguage areas (e.g., recoding, rehearsal, and imagery) in order to defend against L1 entrenchment (Berken et al, ; Hernandez, Claussenius‐Kalman, Ronderos, & Vaughn, ; Hernandez, Li, & MacWhinney, ).…”
Section: Discussionsupporting
confidence: 72%
“…The effects are developmental, dynamic, and non-linear, and are likely the products of different forms of bilingual experiences. Thus it is suggested that future research of the bilingual advantage should not center on whether language experience affects cognitive control or not, but on how language experience at different points in life dynamically affects cognitive control (Li et al, 2014;Hernandez et al, 2018Hernandez et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Future ecological research should consider the tasks of language production and comprehension together, especially for non-balanced bilingual children. Finally, given the latest direction in bilingualism study – i.e., that bilingualism is not a categorical label ( Luk and Bialystok, 2013 ) and should be regarded as a gradient or spectrum of the experience-based dynamic process ( Hernandez et al, 2018 ; DeLuca et al, 2019 , 2020 ; Pliatsikas, 2019 ; Pliatsikas et al, 2019 ; Sulpizio et al, 2020a ) – future studies on the effects of bilingualism on children’s brains should consider complex variables, ecological validity, and tracking paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…The abundant bilingual exposure in this age range may have reconstructed the neural network on the formation of attention-demanding word identification processes to a large extent. The BAPSS theory and Neuroemergentism framework claim that the shift of recruitment from frontal to posterior and subcortical regions is modulated with L2 exposure and learning time (Grundy et al, 2017;Hernandez et al, 2018). In other words, young children who are on the way to learning English perhaps undergo the early stages of neural specialization.…”
Section: Brain Activation Pattern For Word Comprehensionmentioning
confidence: 99%